2016
DOI: 10.18632/oncotarget.12577
|View full text |Cite
|
Sign up to set email alerts
|

Implications of immune dysfunction on endometriosis associated infertility

Abstract: Endometriosis is a complex, inflammatory disease that affects 6-10% of reproductive-aged women. Almost half of the women with endometriosis experience infertility. Despite the excessive prevalence, the pathogenesis of endometriosis and its associated infertility is unknown and a cure is not available. While many theories have been suggested to link endometriosis and infertility, a consensus among investigators has not emerged. In this extensive review of the literature as well as research from our laboratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 105 publications
3
110
0
15
Order By: Relevance
“…These inflammatory responses of the endometrium of endometriosis has important downstream effects that impact fertility (85-90) and have been recently reviewed (5, 91). Interleukin-17 is central to many of the changes in endometriosis including the stimulating effect on cyclooxygenase-2 (Cox-2) activity, IL-8 and aromatase expression (92).…”
Section: Endometriosis and Inflammationmentioning
confidence: 99%
“…These inflammatory responses of the endometrium of endometriosis has important downstream effects that impact fertility (85-90) and have been recently reviewed (5, 91). Interleukin-17 is central to many of the changes in endometriosis including the stimulating effect on cyclooxygenase-2 (Cox-2) activity, IL-8 and aromatase expression (92).…”
Section: Endometriosis and Inflammationmentioning
confidence: 99%
“…Any problem in these systems, such as endometriosis-induced inflammation, impairs reproductive function [18]. Endometriosis characteristically causes chronic intraperitoneal inflammation and may cause infertility by several pathways, including disturbed folliculogenesis, reduced oocyte quality, impaired embryo development, and reduced endometrial receptivity [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone acts through progesterone receptors A and B. Reduced progesterone B receptors disrupt adequate progesterone signaling and this causes progesterone resistance, which is a hallmark for implantation failure [18]. A previous study showed that TNF-α caused a decrease in progesterone A and B receptor expression in the endometrium in women with endometriosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Die Endometriose wird als eine proliferativ-entzündliche Erkrankung angesehen [2,11]. Ätiologisch wird eine biochemische Prägung während der Schwangerschaft und perinatal diskutiert [12,13].…”
Section: äTiologische Erkenntnisseunclassified
“…Eine Belastung mit Xeno-Östrogenen ist mit Endometriose und Myomata korreliert [10,14]. Mit Beginn der Pubertät wird eine Entzündungskaskade ausgelöst, die über die Estradiol-Produktion gesteuert ist [2,[15][16][17][18]. Die biochemische Dysbalance führt oft zu Funktionsstö-rungen wie chronischen Schmerzen sowie Tubentransport-und Einnistungsproblemen.…”
Section: äTiologische Erkenntnisseunclassified